If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 2) + 4(x + 1) = 3x + 8 Reorder the terms: 2(2 + x) + 4(x + 1) = 3x + 8 (2 * 2 + x * 2) + 4(x + 1) = 3x + 8 (4 + 2x) + 4(x + 1) = 3x + 8 Reorder the terms: 4 + 2x + 4(1 + x) = 3x + 8 4 + 2x + (1 * 4 + x * 4) = 3x + 8 4 + 2x + (4 + 4x) = 3x + 8 Reorder the terms: 4 + 4 + 2x + 4x = 3x + 8 Combine like terms: 4 + 4 = 8 8 + 2x + 4x = 3x + 8 Combine like terms: 2x + 4x = 6x 8 + 6x = 3x + 8 Reorder the terms: 8 + 6x = 8 + 3x Add '-8' to each side of the equation. 8 + -8 + 6x = 8 + -8 + 3x Combine like terms: 8 + -8 = 0 0 + 6x = 8 + -8 + 3x 6x = 8 + -8 + 3x Combine like terms: 8 + -8 = 0 6x = 0 + 3x 6x = 3x Solving 6x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6x + -3x = 3x + -3x Combine like terms: 6x + -3x = 3x 3x = 3x + -3x Combine like terms: 3x + -3x = 0 3x = 0 Divide each side by '3'. x = 0 Simplifying x = 0
| s*6+18=156 | | 4=lx+5l | | 380+x=400 | | 5x-2(9+2x)=18 | | 80=x+65+x+45 | | -7x+8(6+2x)=-5 | | -x-5=2x+0 | | Cosx=27 | | 6x-5(20+2x)=12 | | 9xy-12xy= | | x*x-6*x-12=0 | | -9(k+11)=-288 | | 7x+18=85 | | -12-7a=-5(a+4) | | 45=x+62+x+87 | | 9x+13=59 | | 38x+31=563 | | -30-6x=-6(3x-7) | | 17x+6=106 | | 16-3m=7-6(m+2) | | 10x-25=105 | | 80+x=171 | | 34+4x=-5(x+4) | | -3x-3(1+1)=-15 | | 55x=605 | | 2x+-2=10-4 | | 4y+9=17-2y | | 43+x=410 | | x-24=64 | | -3X^2+90=0 | | 5x=430 | | 4x-5y-9x+8y=0 |